1993
DOI: 10.1007/bf02631426
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow stromal cells express an osteoblastic phenotype in culture

Abstract: This study reports the selection and characterization of osteogenic precursors from human bone marrow which were isolated by two "clonings" and successive subculturing. These cell lines express alkaline phosphatase activity. Gel electrophoresis of [3H]-proline labeled cultures showed that the cloned cells produce only type I collagen. They synthetize osteocalcin and osteonectin. They respond to 1,25 dihydroxy vitamin D3 by increasing osteocalcin synthesis and secretion, and to parathyroid hormone by increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 40 publications
3
72
0
Order By: Relevance
“…Although long-term use of pharmacological doses of glucocorticoids results in osteoporosis in vivo, it has been reported that glucocorticoids induce differentiation of osteoprogenitor cells into osteoblasts (Haynesworth et al 1992, Vilamitjana-Amedee et al 1993, Cheng et al 1994. These seemingly paradoxical effects of glucocorticoid can be explained by the inhibition of proliferation of osteoprogenitor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long-term use of pharmacological doses of glucocorticoids results in osteoporosis in vivo, it has been reported that glucocorticoids induce differentiation of osteoprogenitor cells into osteoblasts (Haynesworth et al 1992, Vilamitjana-Amedee et al 1993, Cheng et al 1994. These seemingly paradoxical effects of glucocorticoid can be explained by the inhibition of proliferation of osteoprogenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that bone marrow stromal cells include actively proliferating osteoprogenitor cells, and these cells can be induced to differentiate into cells exhibiting osteoblast phenotype by dexamethasone (Haynesworth et al 1992, Vilamitjana-Amedee et al 1993,Cheng et al 1994. To investigate the mechanisms of bone loss incurred by glucocorticoid administration in humans, we studied the effects of dexamethasone on the proliferation, differentiated activities, and production of bone-resorbing cytokines in normal human bone marrow stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Stromal cells were obtained as described previously [22] and were cultured in Iscove's Modified Dubelcco's Medium (IMDM, Gibco, Grand Island. NY) supplemented with 10% (vlv) of fetal calf serum (FCS, Gibco, Grand Island, NY).…”
Section: Ccdl Prol(fifiration O / Huniuri Hone Murroii' Siromul Wllmentioning
confidence: 99%
“…Their informed consent was obtained. Cells were separated into a single suspension by sequential passage through syringes fitted with 16-, 18-, and 21-gauge needles, cultured in IMDM supplemented with 10% (vol/vol) FCS, 100 U/ml penicillin, and 100 g/ml streptomycin, and incubated in a humidified atmosphere of 95% (vol/vol) air-5% (vol/vol) CO2 at 37°C (42,49). Dexamethasone at 10 Ϫ8 M was added to the culture medium during the first 2 wk of culture to induce alkaline phosphatase stimulation and mineralization of adherent cells (1).…”
Section: Cell Culturementioning
confidence: 99%
“…HBMSC also were characterized by immunocytochemical detection of intracytoplasmic type I collagen and osteocalcin (Takara Biomedicals). Moreover, additional markers besides the latter (osteopontin, calcium-binding proteins, osteonectin) (49) and their responsiveness to vitamin D3 [1,25(OH)2D3 or dihydroxycholecalciferol], parathyroid hormone, transforming growth factor-␤ (TGF-␤), and bone morphogenetic protein 3 (BMP3) have previously been studied (17,18).…”
Section: Cell Culturementioning
confidence: 99%